NEW APPROACH TO JOURNALISM - ALEXANDRA KITTY, AUTHOR (CAMBRIDGE SCHOLARS PUBLIS, 2020)
This ground-breaking textbook finally provides a new approach to journalism. With the Internet and the collapse of traditional journalism created in a pre-social media era, this book presents an alternative through both an empirical and experimental approach. This exciting new model allows a bold new method of connecting with the world, where diversity and multiple perspectives are now the norm. This book shows students a bright new path: one that is narrative-free, and presents verified facts in a simple, interconnected way. We can see how the world interconnects, shifts, changes, evolves, an.